THE ROLE OF AI (ARTIFICIAL INTELLIGENCE) FOR ALZHEIMER: A SYSTEMATIC REVIEW - Ester Rumaseb; Sulistiyani Sulistiyani; Lalu Guntur Payasan (LPPM Nusa Mandiri, 2025)
Alzheimer's disease (AD) is the most common type of dementia and represents a significant global health problem due to its profound impact on patients' quality of life and the heavy burden it places on health care. Alzheimer's is characterized by a progressive decline in cognitive function and memory, ultimately disrupting daily activities and leading to dependence on long-term care. This systematic literature review aims to explore the role of AI in diagnosing and managing Alzheimer’s disease. The method used in this study refers to the PICO framework to highlight various studies on the role of AI for Alzheimer's disease. Recent breakthroughs in the field of artificial intelligence (AI), particularly machine learning (ML) and deep learning, offer promising innovative approaches to improve diagnosis, monitoring, and understanding of Alzheimer's disease.